2021
DOI: 10.3389/fonc.2021.737302
|View full text |Cite
|
Sign up to set email alerts
|

Building Radiomics Models Based on Triple-Phase CT Images Combining Clinical Features for Discriminating the Risk Rating in Gastrointestinal Stromal Tumors

Abstract: We aimed to build radiomics models based on triple-phase CT images combining clinical features to predict the risk rating of gastrointestinal stromal tumors (GISTs). A total of 231 patients with pathologically diagnosed GISTs from July 2012 to July 2020 were categorized into a training data set (82 patients with high risk, 80 patients with low risk) and a validation data set (35 patients with high risk, 34 patients with low risk) with a ratio of 7:3. Four diagnostic models were constructed by assessing 20 clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…In ultrasonography, cystic degeneration and necrosis appear as an intratumoral inhomogeneous echogenicity. Previous studies (27)(28)(29)(30) have shown that the presence of cystic degeneration and necrosis in the mass can be used as reliable indicators for GISTs malignancy evaluation, which is consistent with the results of our study. In this study, the AUC of the clinical ultrasound nomogram for predicting the malignant potential of GISTs was 0.86 in the training cohort and only 0.83 in the validation cohort.…”
Section: Discussionsupporting
confidence: 93%
“…In ultrasonography, cystic degeneration and necrosis appear as an intratumoral inhomogeneous echogenicity. Previous studies (27)(28)(29)(30) have shown that the presence of cystic degeneration and necrosis in the mass can be used as reliable indicators for GISTs malignancy evaluation, which is consistent with the results of our study. In this study, the AUC of the clinical ultrasound nomogram for predicting the malignant potential of GISTs was 0.86 in the training cohort and only 0.83 in the validation cohort.…”
Section: Discussionsupporting
confidence: 93%
“…Several prior studies have reported the satisfactory performance of CT-based radiomics in the diagnosis and prediction of the malignant potential of GISTs[ 17 , 37 - 39 ]. Starmans et al [ 40 ] documented that the radiomics model achieved an AUC of 0.77 in distinguishing GISTs from non-GISTs, yielding results comparable to those of radiologists but with reduced observer dependence.…”
Section: Discussionmentioning
confidence: 99%